The february–march 2000 eruption of Hekla, Iceland from a satellite perspective - Rose, William I.; Gu, Y.; Watson, M. I.; Yu, T.; Bluth, Gregg J.; Prata, A. J.; Krueger, A. J.; Krotkov, N.; Carn, S.; Fromm, M. D.; Hunton, D. E.; Ernst, G. G. J.; et al. (Digital Commons @ Michigan Tech, 2013)
An 80,000 km2 stratospheric volcanic cloud formed from the 26 February 2000 eruption of Hekla (63.98° N, 19.70° W). POAM-III profiles showed the cloud was 9–12 km asl. During 3 days this cloud drifted north. Three remote sensing algorithms (TOMS SO2, MODIS & TOVS 7.3 μm IR and MODIS 8.6 μm IR) estimated ~0.2 Tg SO2. Sulfate aerosol in the cloud was 0.003–0.008 Tg, from MODIS IR data. MODIS and AVHRR show that cloud particles were ice. The ice mass peaked at ~1 Tg ~10 hours after eruption onset. A ~0.1 Tg mass of ash was detected in the early plume. Repetitive TOVS data showed a decrease of SO2 in the cloud from 0.2 Tg to below TOVS detection (i.e.<0.01 Tg) in ~3.5 days. The stratospheric height of the cloud may result from a large release of magmatic water vapor early (1819 UT on 26 February) leading to the ice-rich volcanic cloud. The optical depth of the cloud peaked early on 27 February and faded with time, apparently as ice fell out. A research aircraft encounter with the top of the cloud at 0514 UT on 28 February, 35 hours after eruption onset, provided validation of algorithms. The aircraft’s instruments measured ~0.5–1 ppmv SO2 and ~35–70 ppb sulfate aerosol in the cloud, 10–30% lower than concentrations from retrievals a few hours later. Different SO2 algorithms illuminate environmental variables which affect the quality of results. Overall this is the most robust data set ever analyzed from the first few days of stratospheric residence of a volcanic cloud.